Análisis de la rentabilidad del Comercial Villacres años 2018 y 2019 - Mayorga Sandoya, Daily Ginett (2020)
Remuneration that a company (in the broad sense of the word) is able to give to the different elements made available to it to carry out its economic activity. It is a measure of the effectiveness and efficiency in the use of these financial, productive and human elements. The Villacrés commercial is located in the CENTRAL COAST, in the Province of Los Ríos, in the city of VENTANAS, it has been conceived since its inception to support the agricultural development of the agro-productive area of influence, it has been in the market for 13 years, It started its activity with a small investment and is currently considered one of the commercial companies with the highest demand. Its mission is to collect cereals and oilseeds to give the appropriate treatment. This case study aims to analyze the profitability of Comercial Villacrés during the 2018 - 2019 period through a horizontal and vertical analysis of the different accounts that are in the Statement of Financial Position and the Statement of Comprehensive Income during the mentioned years, in which the financial indices will also be applied, but essentially the methods that will allow determining the economic performance of Comercial Villacrés. Despite obtaining important values in terms of gross income, which in the two periods subject to analysis (2018 and 2019) exceeds three million US dollars, however, the profitability margin is lower than normally expected based on to the economic and financial efforts made.